2020
DOI: 10.1186/s12882-020-01964-w
|View full text |Cite
|
Sign up to set email alerts
|

An unusual presentation of propylthiouracil-induced anti-MPO and PR3 positive ANCA vasculitis with associated anti-GBM antibodies, IgA nephropathy and an IgG4 interstitial infiltrate: a case report

Abstract: Background: A number of disease processes can culminate in rapidly progressive glomerulonephritis, including pauci-immune focal segmental necrotising glomerulonephritis, usually seen with positive serum antineutrophil cytoplasmic antibodies (ANCA). Propylthiouracil (PTU) has been associated with drug-induced ANCA-associated vasculitis (AAV), with antibodies against myeloperoxidase (MPO) and proteinase 3 (PR3) present individually and together having been recognised. 'Double-positive' vasculitis with ANCA and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Concurrent subacute presentation of IgG4-related kidney disease with ANCA-associated MPO crescentic glomerulonephritis is uncommon, with cases reporting these simultaneously presenting diagnoses only surfacing over recent years ( Table 1 ) [ 9 , 10 , 11 , 12 , 13 , 14 ]. In 2017, Su et al [ 10 ] reported the first case of concurrent IgG4-related tubulointerstitial nephritis with ANCA-associated MPO crescentic glomerulonephritis in a 42-year-old Chinese man.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent subacute presentation of IgG4-related kidney disease with ANCA-associated MPO crescentic glomerulonephritis is uncommon, with cases reporting these simultaneously presenting diagnoses only surfacing over recent years ( Table 1 ) [ 9 , 10 , 11 , 12 , 13 , 14 ]. In 2017, Su et al [ 10 ] reported the first case of concurrent IgG4-related tubulointerstitial nephritis with ANCA-associated MPO crescentic glomerulonephritis in a 42-year-old Chinese man.…”
Section: Discussionmentioning
confidence: 99%
“…These cases have mostly been related to drugs or systemic disease [ 6 – 8 ]. Although certain drugs, such as propylthiouracil, may play a role in the pathogenesis of AAV [ 9 , 10 ], the relationship between most drugs and ATIN associated with ANCA is tentative and the pathological mechanisms are unknown. Most cases of drug-induced AAV improve after withdrawal of the suspected drug, but in severe cases, steroids may be required [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Drugs may also trigger AAV and IgAN (2,36). Galante et al described the coexistence of AAV and IgAN triggered by propylthiouracil (19). According to the authors' hypothesis, propylthiouracil-induced AAV resulted in an infiltration of IgG4rich cells in the tubulointerstitial tissue as well as epiphenomena of anti-GBM antibody production.…”
Section: Discussionmentioning
confidence: 99%